Transcriptional and hormonal profiling of Fusarium graminearum-infected wheat reveals an association between auxin and susceptibility. (August 2019) - Brauer, Elizabeth K.; Rocheleau, Hélène; Balcerzak, Margaret; Pan, Youlian; Fauteux, François; Liu, Ziying; Wang, Li; Zheng, Wenju; Ouellet, Thérèse
Abstract: Resistance to Fusarium graminearum, a fungal pathogen of cereals, has been associated with increased defense-associated hormonal responses in wheat. A comparison of susceptible (Roblin) and moderately resistant wheat genotypes (Wuhan 1, Nyubai) revealed transcriptional regulation of 1021 genes during infection. Only 4% of these genes were uniquely differentially expressed in the susceptible genotype including an auxin transporter, an ABC transporter, and transcription factors. Roblin displayed higher auxin accumulation during infection relative to resistant genotypes, but similar levels of salicylic acid and jasmonic acid. This indicates that the auxin pathway is one of the few susceptibility-associated pathways during F. graminearum infection. Highlights: Global gene expression profiles and hormone production following Fusarium graminearum inoculation in wheat genotypes. Only 4% of genes were differentially expressed in susceptible vs resistant genotypes. Auxin production was associated with susceptibility to FHB. Auxin production was likely from the wheat tissues.